Nephroma congenital mesoblastic. - Pereda Garay, José (2015)
In children, the most common renal tumor is the nephroblastoma or Wilms tumor. This does not happen in the newborn or fetus, although it is true that they can be found proliferative lesions that resemble Wilms tumor, such as nephroblastomatosis, the monomorphic epithelial nephroblastoma and mesoblastic nephroma (11) all of which They are grouped under the name of childhood Wilms congeners. In this group, a tumor that has well-defined characteristics, which is relevant check is called mesoblastic nephroma. A case that was recently observed in the Laboratory of Pathology of the Maternity Hospital of Lima in order to encourage the study of this entity and discuss some aspects considered interesting to discuss is presented.